The Effect of Misalignment to Vibration, Electric Current and Shaft Rotation Speed on Gear Transmission - Romiyadi Nawir; Yudi Dwianda; Adi Febrianton; Purnama Irwan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
Gear is a rotating machine that is widely used as a power transfer transmission in many industries. Gear has a long life times. However, the gears can be damaged due to many factors such as out of the maintenance, which one factor of misalignment. This study aim is to determine the effect of misalignment on the gear transmission to vibration, electric current and shaft rotation speed. In this study, was done alignment process with variations of misalignment on the gear transmission alignment kit and was done measurement value of vibration, electric current and shaft rotation speed. The study results show the greater the misalignment, the greater the vibration that occurs either radially or axially for all conditions measured. The shaft rotation was slower with the greater misalignment. The misalignment can affect the decrease in the rotation speed of the shaft. Therefore, it can reduce the efficiency for power transmission of engine.